Trace elements in Gobi soils of the northeastern Qinghai-Tibet Plateau. Issue 10 (25th November 2020) - Li, Leiming; Wu, Jun; Lu, Jian; Xu, Juan
ABSTRACT: This study investigated the pollution, potential ecological risks, and possible sources of trace elements in Gobi soils of the northeastern Qinghai-Tibet Plateau. Contents of Hg in soils were below the detection limit. The average contents of the remaining trace elements in soils ranged from 0.21 (Cd) to 2360.82 (As) mg/kg. Multiple methods were used to evaluate the soil pollution of the study area. Pb posed the most serious pollution based on geo-accumulation index evaluation. As showed the strongest enrichment feature according to enrichment factor method. Compared with pollution load index and modified contamination degree, Nemerow pollution index results obtained the most serious evaluation on pollution that 10% and 40% of sampling sites possessed moderate and high pollution, respectively. Trace elements in soils posed high ecological risks in 20% of sampling sites. Pearson's correlation matrix and principal component analysis were used to determine that anthropogenic activities such as industrial and mining activities might be the main source for several trace elements. This study will provide important information on soil quality control in the northeastern Qinghai-Tibet Plateau, especially the area with little vegetations.